The polyA regions of hen oviduct RNA - Dornan, Valerie (1974)
Total RNA from hen oviduct has been hydrolysed with a mixture of T(1) and pancreatic ribonucleases. Poly(A) tracts in the digestion product have been isolated by binding to oligo(dT) cellulose. Of the four major ribonucleotides, the product has been shown to contain only adenylic acid. When separated on polyacrylamide gels, the poly(A) gave two peaks corresponding to average apparent lengths of 270-280 and 540-550 nucleotides.